KAJIAN BEBERAPA VARIETAS UNGGUL BARU DAN SISTEM TANAM JAJAR LEGOWO PADI SAWAH DI DATARAN TINGGI SUNGAI PENUH JAMBI - Syafri Edi; Defira Suci Gusfarina (Bioplantae, 2013)
ABSTRACT The use of new varieties and legowo row planting system is a component of integrated crop management technology and be a deciding factor to increase production and productivity of rice plants, and is an easy technology to apply by farm level. This study aims to obtain new varieties and legowo row of upland rice planting systems in Jambi Province. Research conducted at the Sungai Penuh District, Jambi Province from June to November 2013, at an altitude of 938 m above sea level with the type of soil andosol. The project used randomized group of two factors. The first factor is the new varieties of paddy, (1) Inpari 21 (2) Inpari 28, and (3) Batang Piaman. Factor II is cropping systems, (1) Jajar legowo 2 : 1, and (2) Jajar legowo 4 : 1. The results showed that legowo row planting system 2 : 1 and 4 : 1 has not showed significant differences in all variables were observed, except observation of the dry grain yield harvest, where Inpari 28 gives the highest yield in legowo row planting system 2 : 1. The high yield result of Inpari 28 supported by the component that is relatively better results compared to Inpari 21 and varieties Batang Piaman with legowo row planting systems 2 : 1 or 4 : 1. The three varieties and two cropping systems tested were able to provide results > 5 t/ha and higher than 2013 BPS report, however, needs further research on a larger scale before it developed by the farmer. Keywords: new superior varieties, paddy, plateau, cropping systems, Jambi